ANALISIS KINERJA KEUANGAN PERUSAHAAN MENGGUNAKAN DU PONT SYSTEM (Studi Kasus Pada PT. Buana Finance Tbk, PT. BFI Finance Indonesia Tbk Dan PT. Clipan Finance Tbk Yang Terdaftar Di Bursa Efek Indonesia Periode 2011-2014) - Fauziah, Nanda; Farida, Lena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Financial performance evaluation of activities is very important for the company. Methods used to measure the financial performance of any of them is a Du Pont System. Du Pont System is Methode for measuring financial performance involving some of the ratio,there are the ratio of profitability and the ratio of activity. The purpose of this research to know the company financial PT. Buana Finance Tbk, PT. BFI Finance Indonesia Tbk and PT. Clipan Finance Tbk by using Du Pont System method in trend analysis. The result showed that the performance of PT. Buana Finance Tbk, seen in ROE and ROI tended to decline during the period 2009-2013.But PT. BFI Finance Indonesia Tbk and PT. Clipan Finance Tbk experience fluctuation. ROE who fluctuating is caused by several things , among them is inefficiency in the total cost increases and not balanced with the EAT , NPM that fluctuating for five years. Infesiensi also occurred in total assets , which increased by that is not balanced with the value of sales , resulting in TATO fluctuative. Companies should make improvements at the level of sales and total assets, also do efficiency in expense and debt.Keyword: Trend Analysis, Net Profit Margin (NPM), Total Assets Turn Over (TATO), Return On Investment (ROI), Return On Equity (ROE)